Multicriteria analysis for the selection of the most appropriate energy crops: the case of Cyprus. Issue 1 (2nd January 2016) - Kylili, Angeliki; Christoforou, Elias; Fokaides, Paris A.; Polycarpou, Polycarpos
Abstract : Energy crops are considered key actors in meeting the international and European carbon reduction targets, increasing the national energy security through renewable energy production, mitigating climate change impacts, and promoting sustainability. Multicriteria analysis is a suitable decision-making tool for the energy sector, where the final decisions have to consider for a range of aspects, and can be utilised as well for deciding on appropriate energy crops. In this paper, a popular multicriteria method, PROMETHEE, is employed for the identification of the most optimal energy crops for their exploitation in Cyprus. The criteria and the weights of each are defined, and accordingly five different scenarios are developed and examined. The obtained results indicated that the promotion of second-generation energy crops is more ideal in terms of the set objectives, as well as more sustainable than the exploitation of any first-generation energy crop.